Electronic properties of surface vacancies in CdS nanocrystals - I. M. Kupchak (Фізика і хімія твердого тіла, 2018)
Structural and electronic characteristics of neutral and charged vacancies of cadmium and sulfur in CdS nanocrystals have been performed using the density functional method with hybrid exchange-correlation functional. Total and partial density of states, formation energies and the energies of thermodynamic transitions were calculated. Based on these theoretical findings and available experimental data, we can confirm the assumption, that the singly charged vacancies of cadmium are the centers of radiative recombination in such the structures. Key words: Cadmium sulfide, nanocrystal,  photoluminescence, vacancy, density functional method.